The mapping of information landscapes as a tool to develop IL - Whitworth, Andrew (Septentrio Conference Series, 2020)
In her discussion of information literacy, Annemaree Lloyd (2010) developed the notion of the information landscape as a way of conceptualising the informational and technological resources arrayed around individuals and groups, and which they must learn to navigate. She alludes (p. 2) to the idea of mapping this landscape as a way by which actors learn these navigational skills and, thus, develop information literacy. But she offers no detail in this work or others regarding what mapping might actually mean as an educational practice, and how it might be employed in the teaching and learning of information literacy. This paper will report on research conducted on data generated in different ways from a course in which mapping is integrated, as both a graphical and discursive practice. At the start of this course, students are asked to collaborate on drawing mind maps that depict their information landscape as they see it at this point, and these maps can be analysed as depictions of their information horizons, in ways similar to the study of Sonnenwald, Wildemuth and Harmon (2001). In addition, data have been generated from online discussions undertaken throughout the course, which record how within small groups, students negotiate and build the information landscape that they use to complete the course assessment. By suggesting and/or validating the judgments of members, the group develops an agreed-upon representation of their landscape that can be the basis for further judgments. Thus, from the dialogue emerges a discursive map of this landscape. It will be argued that the process of negotiating this map is a productive one when considering how information literacy sklills can be developed in ways that will transfer effectively outside the university.